Heavy Metal Music in Latin America: Perspectives from the Distorted South - Varas-Díaz, Nelson; Araújo, Daniel Nevárez; Rivera-Segarra, Eliut (Lexington Books, 2020)
In Heavy Metal Music in Latin America: Perspectives from the Distorted South, the editors bring together scholars engaged in the study of heavy metal music in Latin America to reflect on the heavy metal genre from a regional perspective. The contributors’ southern voices diversify metal scholarship in the global north. An extreme musical genre for an extreme region, the contributors explore how issues like colonialism, dictatorships, violence, ethnic extermination and political persecution have shaped heavy metal music in Latin America, and how music has helped shape Latin American culture and politics.